The politics of empowerment: power, populism and partnership in rural Ireland - Varley, Tony; Curtin, Chris (Economic & Social Studies, 2006)
Since the early 1990s local area partnerships, sponsored either by the state or by the EC/EU together with the state, have proliferated in Ireland as elsewhere (Geddes, 2000). What inspired these area partnerships initially was an official analysis that the conditions resulting in urban and rural decline had reached crisis dimensions that cried out for a fresh policy response. The basic idea was to tackle intractable economic and social problems by creating institutional arrangements capable of producing a consensus among key actors and of harnessing the energies of the public, private and voluntary sectors in new dynamic area partnerships.
This paper was delivered at a conference ?Social Partnership: A New Kind of Governance?? funded by the Irish Research Council for the Humanities and Social Sciences, National Institute for Regional and Spatial Analysis and the Department of Sociology, NUI Maynooth, 14-15 September 2004.
Keywords: Governance; Social partnership; Ireland; Regional planning